2001
DOI: 10.1093/jn/131.3.723
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Isoflavones Dose-Dependently Reduce Bone Turnover but Do Not Reverse Established Osteopenia in Adult Ovariectomized Rats

Abstract: We assessed the dose-dependent effects of daily soybean isoflavone (IF) consumption in reversing bone loss in adult ovariectomized rats. On d 0, female Wistar rats (7 mo old; n = 55) were either sham-operated (SH; n = 14) or ovariectomized (n = 41). On d 80, intermediate rats (SH: n = 5; ovariectomized: n = 5) were killed to confirm the ovariectomy-induced bone loss. The remaining ovariectomized rats were randomly assigned to one of four groups of nine rats each and fed soybean IF (mixed with a soy protein-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 21 publications
4
53
1
1
Order By: Relevance
“…Our results confirmed the findings of others that the OVX rat model was characterized by high bone turnover rate [20][21][22] and that FLL extract could effectively prevent the OVXinduced increase in bone turnover. The increase in bone turnover was the result of increase in both bone formation and bone resorption associated with E 2 deficiency.…”
Section: Discussionsupporting
confidence: 92%
“…Our results confirmed the findings of others that the OVX rat model was characterized by high bone turnover rate [20][21][22] and that FLL extract could effectively prevent the OVXinduced increase in bone turnover. The increase in bone turnover was the result of increase in both bone formation and bone resorption associated with E 2 deficiency.…”
Section: Discussionsupporting
confidence: 92%
“…Whereas estrogen prevent bone loss by reducing bone resorption, 28,29) the isoflavones genistein and ipriflavone, are antiresorptive only at chronic high doses and therefore have been reported to either inhibit or not affect the bone turnover rate. 30,31) Interestingly, neither of these isoflavones blocks the elevated bone resorption rates induced by ovariectomy or menopause. 32,33) Thus while isoflavone treatment may prevent bone loss, in part, because the enhanced bone formation exceeds resorption, the mechanism underlying the enhanced bone formation by isoflavone treatment in vivo is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…That is, a drastic change in bone turnover markers is observed in advance of change in bone mineral contents, especially shortly after OVX. Picherit et al 36) reported that the urine DPD level increased by 1.5-fold at 5.7 weeks after OVX and returned to the baseline at 11 weeks. Serum osteocalcin level also increased by 1.6-fold at 5.7 weeks, and returned to the baseline at 17 weeks.…”
Section: Discussionmentioning
confidence: 99%